2014
DOI: 10.1093/hmg/ddu537
|View full text |Cite
|
Sign up to set email alerts
|

Becker muscular dystrophy severity is linked to the structure of dystrophin

Abstract: In-frame exon deletions of the Duchenne muscular dystrophy (DMD) gene produce internally truncated proteins that typically lead to Becker muscular dystrophy (BMD), a milder allelic disorder of DMD. We hypothesized that differences in the structure of mutant dystrophin may be responsible for the clinical heterogeneity observed in Becker patients and we studied four prevalent in-frame exon deletions, i.e. Δ45-47, Δ45-48, Δ45-49 and Δ45-51. Molecular homology modelling revealed that the proteins corresponding to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 78 publications
2
77
1
1
Order By: Relevance
“…deletions of exons 45-47, 45-48, 45-49 and 45-51 and the in vitro biochemical status of the proteins [76]. We showed that the structure of the new dystrophins as produced in these BMD patients could partly explain the differences in the clinical severity of the patients.…”
Section: Dystrophin and Dmd Therapymentioning
confidence: 77%
“…deletions of exons 45-47, 45-48, 45-49 and 45-51 and the in vitro biochemical status of the proteins [76]. We showed that the structure of the new dystrophins as produced in these BMD patients could partly explain the differences in the clinical severity of the patients.…”
Section: Dystrophin and Dmd Therapymentioning
confidence: 77%
“…The patients could survive until very old ages or some of them could die from an early heart failure [8,9]. Although the underlying mechanism of this variability is not fully understood, it is likely that both levels and functionality of the internally deleted dystrophins play a significant role [10]. Anthony et al [11] suggested that the patients with BMD who have milder phenotypes have higher expression levels of dystrophin.…”
Section: Discussionmentioning
confidence: 99%
“…If the dystrophin levels are greater than the threshold level (about 30%), then the structural characteristics of the internally deleted dystrophins, rather than the quantity of the dystrophin, could affect the phenotype [13]. Therefore, the structure modifications of dystrophin determined by the site of deletion in addition to its expression level modulate the severity of BMD [10].…”
Section: Discussionmentioning
confidence: 99%
“…Les travaux de Chamberlain sur les micro-dystrophines et mini-dystrophines ont permis de préciser les exons néces-saires et les exons indispensables permettant de maintenir une dystrophine fonctionnelle [12]. La perte d'interaction avec ses partenaires, l'effet « modificateur » de variants sur d'autres gènes et le retentissement sur la configuration secondaire et tertiaire de la quasi-dystrophine issues de mutations non-tronquantes sont autant de pistes prometteuses qui permettront non seulement de comprendre la variabilité phénotypique au sein des dystrophinopathies [11,26] mais aussi de sélectionner les quasidystrophines les plus optimales dans le cadre du saut d'exon thérapeutique. Dans cette optique, nous avons développé eDystrophin, une banque de données librement accessible sur internet et interactive permettant non seulement de prédire les conséquences structurales des mutations du gène DMD conservant le cadre de lecture mais aussi leurs conséquences phénotypiques et protéi-ques observées chez les patients qui en sont porteurs.…”
Section: Rabah Ben Yaou Aurélie Nicolas France Leturcq éLisabeth Lunclassified